Case study: The development of environmental health awareness in Adiwiyata elementary school students - Kumariyah Kumariyah; Sumaryanto; Ngatman; Enggisata Hendriko Delano; Zaza Afnindar Fakhrurozi (Public Health of Indonesia, 2026)
Background: Environmental education is crucial for fostering healthy and clean behaviors. Clean and healthy living behaviors are one of the key missions of health development in Indonesia, which can be achieved through the instillation of education about the importance of such behaviors in children, starting as early as possible. Objective: This study aims to analyze: environmental awareness policies, environmental-based curriculum, participatory school activities in the field of environmental education, and management of environmentally friendly school facilities and infrastructure at Trisik State Elementary School. Methods: This research is a qualitative research with a case study approach. The study is located at SD Negeri Trisik, Kulon Progo, Yogyakarta. The subjects of this study are upper-grade students. Data collection techniques were conducted using purposive sampling. The data sources for this study were obtained from interviews, literature studies, and observations. The validity of the data in this study was ensured through source triangulation and technique triangulation. The data analysis technique used was interactive data analysis, following the framework proposed by Miles & Huberman, which includes data reduction, data presentation, data verification, and conclusion drawing. Results: The results of this study indicate that the development of environmental health awareness at Trisik State Elementary School is carried out through: Establishing policies and programs that support Adiwiyata, such as the SEMUTLIS and AMERTA programs, implementing an environmental-based curriculum through integration in the learning process, implementing a participatory school system in the field of Environmental Education and Learning, implementing environmentally friendly management practices for school facilities and infrastructure. Conclusion: Based on the results of the research and discussion conducted, it can be concluded that environmental education is crucial in promoting clean and healthy living behaviors. The Adiwiyata school program is closely related to education and environmental health, aiming to instill awareness of the importance of the environment among students through various policies, programs, and activities, as seen at SD Negeri Trisik, Kulon Progo.